Cardiorespiratory physiotherapy as a career choice—perspective of students and physiotherapists in Portugal. (2nd November 2019) - Marques, Alda; Oliveira, Ana; Machado, Ana; Jácome, Cristina; Cruz, Joana; Pinho, Tânia; Hall, Andreia; Alvelos, Helena; Brooks, Dina
ABSTRACT: We investigated Portuguese physiotherapy students' and physiotherapists' (1) perceptions of cardiorespiratory physiotherapy (CRP); (2) factors that influenced their decision to pursue a career in CRP; and (3) suggestions to develop CRP. Online surveys were disseminated to final year students and physiotherapists. A number of 189 students (mean age 23 [SD 6] years; 78% ♀) and 375 physiotherapists (mean age 31 [SD 8] years; 78% ♀) participated. Students' opinions about CRP were positively influenced by lecturers ( n  = 112, 69%), clinical experiences ( n  = 110, 68%), and scientific evidence ( n  = 93, 57%). Only 13% of students were "extremely interested" in specializing in CRP. Interest in the area and clinical exposure were the main factors influencing students to pursue a career in CRP. A percentage of 15 of responding physiotherapists were working in CRP. Their decision to pursue a CRP career was most influenced by their interest in the area ( n  = 37, 67%) and opportunity to work in acute settings ( n  = 31; 56%). Main suggestions to develop CRP were (1) include placements in CRP; (2) emphasize health promotion within the curriculum; and (3) develop CRP skills in broader contexts and training. Strategies focusing on changing the curriculum, increasing exposure to CRP, providing good mentorship, developing health promotion activities, and creating postgraduate courses may increase the attractiveness for CRP.